Deixis In Story Snow White And Seven Dwarfs - Dewi Sri Rezeki; Cinta Taufika Anandra; Emely Sukma Dara; Ruri Cendrakasih; Yayank El Azhar (Publikasi Indonesia, 2022)
The research method uses qualitative research in collecting and selecting data for research. Data based on Levinson's theory analysis `The object of this research is utterances that contain deixis in the story of Snow White. The research question of this investigation is what kind of deixis is found in the film Snow White and how is deixis used in the film. Deixis is one of the linguistics forms in pragmatics that can help the reader or speaker to understand the meaning of an utterance. In studying deixis means learning one aspect of natural language to require the reference of who are the speaker and the hearer, the place and the time of speaking in which the deictic word used. Many language phenomena use deixis, such as poem, lyric, film, novel, talk show, and also advertisement. In our daily life, we always find advertisement around us, such as in magazine, newspaper, internet, radio, or television.Based on the findings, it us conclude that there are 5 types of deixis there are person,deixis, place deixis, time deixis, discourse deixis and speech deixis.